2017
DOI: 10.1186/s12893-017-0261-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic sarcopenia predicts postoperative infectious complications in patients undergoing pancreaticoduodenectomy

Abstract: BackgroundRecently, skeletal muscle depletion (sarcopenia) has been reported to influence postoperative outcomes after certain procedures. This study investigated the impact of sarcopenia on postoperative outcomes following pancreaticoduodenectomy (PD).MethodsWe performed a retrospective study of consecutive patients (n = 219) who underwent PD at our institution between January 2007 and May 2013. Sarcopenia was evaluated using preoperative computed tomography. We evaluated postoperative outcomes and the influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 31 publications
(35 reference statements)
2
36
1
Order By: Relevance
“…investigated the relationship between pre‐operative skeletal muscle mass and complications after pancreaticoduodenectomy. They found sarcopenia to be independently associated with infectious complications, including CR‐POPF, wound infection, and intra‐abdominal abscess, but found no significant relationship between skeletal muscle mass and DGE . In the current study, we found an independent association between pre‐operative sarcopenia and post‐pancreaticoduodenectomy DGE; however, the mechanisms by which sarcopenia increases the risk of DGE are unclear.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…investigated the relationship between pre‐operative skeletal muscle mass and complications after pancreaticoduodenectomy. They found sarcopenia to be independently associated with infectious complications, including CR‐POPF, wound infection, and intra‐abdominal abscess, but found no significant relationship between skeletal muscle mass and DGE . In the current study, we found an independent association between pre‐operative sarcopenia and post‐pancreaticoduodenectomy DGE; however, the mechanisms by which sarcopenia increases the risk of DGE are unclear.…”
Section: Discussioncontrasting
confidence: 72%
“…However, the mechanisms by which sarcopenia increases the risk of post‐operative morbidity are unclear. Some studies have specifically evaluated the relationship between pre‐operative sarcopenia and post‐pancreaticoduodenectomy DGE . Takagi et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the image analysis was based on CT, and the third lumbar vertebra was the most commonly used level. SMI/ TAMA was the most commonly used index, and it was used in 16 studies [11, 13, 19, 21, 23-28, 32, 34, 36-39], with SBI in 2 studies [40,42], PMI/TPA in 7 studies [12,20,22,[29][30][31]33], MA/RA in 5 studies [13,24,37,38,41], IMAC in 4 studies [20,27,31,33], HUAC in 1 study [35], LPMA in 1 study [14], and TPV in 1 study [12] ( Table 3).…”
Section: Definition Of Sarcopeniamentioning
confidence: 99%
“…Surgical procedures (Table 1), operative time, intraoperative blood loss, and blood transfusion were recorded as intraoperative outcomes. Details of the surgical techniques of hepatectomy, pancreaticoduodenectomy, and hepatopancreatectomy have been reported previously [11][12][13][14]. At our center, age is not recognized as a contraindication.…”
Section: Clinical Datamentioning
confidence: 99%